Predictive Ability of Managerial Effectiveness and Credit Risk on Market Performance of Manufacturing Industry - Cry Cinta Putri Anjel; Hanna Gratia Kambey; Fanny Soewignyo (Publikasi Indonesia, 2024)
This study aims to evaluate the managerial effectiveness and credit risk in predicting the market performance of non-cyclical sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The number of samples is 38 companies so the total observation data is 190 data on 38 companies. This study uses a causal descriptive design approach where the measurement of managerial effectiveness uses return on net operating assets and credit risk is measured by debt to equity ratio. While measuring market performance using Tobin's Q. The study used RNOA to measure managerial effectiveness, Tobin's Q to measure market performance and DER to measure credit risk. The results of the study show that 88.1% variation in the value of Tobin's Q in non-cyclical sector companies listed on the IDX can be explained by the return on net operating assets RNOA and debt to equity ratio DER. which indicates that managerial effectiveness and credit risk play a crucial role in determining the company's market performance. Partially, the return on net operating assets of RNOA had a significant negative effect on Tobin's Q and the debt-to-equity ratio DER had a significant positive effect on Tobin's Q.